The Meaning of the Philosophical Calling according to Socrates and Heidegger - De Bravo Delorme, Cristián (2022)
According to the allegory of the cave and the experience of the liberation of the prisoner described there, philosophy implies a redirection of human life. This redirection is not subject to the will of the person who experiments it; therefore, it cannot be self-procured, but rather occurs through the violent action of another. This violence highlights that philosophy arises from a relationship between one who provokes this experience and another who experiences it; and, in addition, that this experience entails a transformation of existence. This experience seems and a certain attitude that suggest —insofar they are provoked violently— the unavailability of the philosophical experience come here to the foreground. The following paper attempts to outline the meaning of the philosophical calling according to Socrates and Heidegger, and to understand to what extent the transformation that is generated here sets in motion not only two different ways of philosophising, but also two ways of being that seem conciliable to some degree, though they turn out to be ultimately incompatible, to come close to the one discussed by Heidegger in his analysis of the existentialmodification from the They-Self to the authentic Self. Additionally, a relationship.